2015
DOI: 10.3329/bjvm.v13i1.23710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diclofenac Sodium in Broilers

Abstract: This study was conducted to determine the effects of diclofenac sodium in broiler chicks during the period from 20 th July /2012 to 1 st september/2012. The broiler chicks were divided into four groups A, B, C and control with ten day old bird in each. Group A was treated with @ 5mg/kg body weight, group B was treated with @ 10mg/kg body weight and Group C was treated with 20 mg/kg body weight given orally mixing with drinking water. Histopathological, hematological and biochemical tests were performed on 42 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…For animals, 1-18 mg/kg DS doses were used in teratogenic studies related to pregnancy [3,6,19,44]. A toxic dose of DS was 5 mg/kg in avian species [1,33]. Four doses were tested: first dose, 1/20 of the toxic dose = 0.25 mg/kg; second dose, 1/10 of the toxic dose = 0.5 mg/kg; third dose, 1/5 of the toxic dose = 1 mg/kg; and fourth dose, 1/2.5 of the toxic dose = 2 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…For animals, 1-18 mg/kg DS doses were used in teratogenic studies related to pregnancy [3,6,19,44]. A toxic dose of DS was 5 mg/kg in avian species [1,33]. Four doses were tested: first dose, 1/20 of the toxic dose = 0.25 mg/kg; second dose, 1/10 of the toxic dose = 0.5 mg/kg; third dose, 1/5 of the toxic dose = 1 mg/kg; and fourth dose, 1/2.5 of the toxic dose = 2 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Diclofenac is a non-steroidal anti-inflammatory drug. The toxicokinetic in quail has belonged to metabolic capacity with t1/2 and mean residence time MRT above 8 hours with apparent signs of toxicities (2)(3)(4). Study of pharmacokinetics for enrofloxacin and ciprofloxacin in cow and steers showed the plasma elimination half-life for two drugs were longer in steers lactating cow than in cow (5).…”
Section: Introductionmentioning
confidence: 99%
“…The liver function markers AST and ALT were significantly increased in the birds effected with gout induced by high protein diet (Hong F et al, 2020) and diclofenac (Sandhyarani et al, 2019) which is an indication of hepatic injury. Antioxidant profile reveals decreased glutathione stimulating hormone (GSH) and increased thiobarbituric acid reactive substances (TBARS) in kidney and liver tissue (Singh et al, 2013;Akter and sarker, 2015;Sandhyarani et al, 2019). Glutathione (GSH) is an important intracellular peptide with multiple functions ranging from…”
Section: Clinical Pathologymentioning
confidence: 99%
“…Microscopically, marked congestion, hameorrhages involving glomeruli, cortical and medullary tubules, collecting ducts and medullary tracts and focal to diffuse degenerative changes in tubular epithelium like vacuolar degeneration, desquamated and necrosed tubular epithelial cells. Kidney parenchyma exhibited aggregates of uric acid crystals characterized by needle shaped urate crystals as pink radiating amorphous material surrounded by a narrow zone of inflammatory cells (Muhammed et al, 2012;Bulbule et al, 2013;Akter and sarker, 2015). Chandra and Balwant (1980) described the extent of damages to kidney was directly correlated to the degree of urate deposition.…”
Section: Postmortem Lesionsmentioning
confidence: 99%
See 1 more Smart Citation